Strategi Adaptasi Ekosistem Mikro terhadap Fenomena Urban Heat Island di Kawasan Perkotaan - Rahmi Alfitra Najwa; Faidzul Bayani; Hari Setianto (Trends Research of Environmental Studies, 2025)
The urban heat island (UHI) phenomenon represents one of the significant impacts of intensive urbanization and land cover change in urban areas. The increase in temperature affects not only human thermal comfort but also directly influences the stability and functioning of urban ecosystems, particularly at the micro scale. This study aims to examine the characteristics of UHI at the micro scale and to analyze the adaptive responses of micro-ecosystems in coping with rising temperatures in urban areas. This research employs a quantitative approach supported by spatial and ecological analyses, integrating remote sensing data, field-based microclimate measurements, and vegetation and soil analyses. The results indicate that UHI intensity is heterogeneously distributed across urban spaces and is strongly influenced by land cover, vegetation structure, and soil moisture conditions. Micro-ecosystems with well-developed vegetation, moist soils, and stable microorganism activity exhibit higher adaptive capacity to temperature stress. Vegetation plays a crucial role in reducing temperature through shading and evapotranspiration mechanisms, while soil and microorganisms contribute to maintaining the balance of ecological functions. This study confirms that adaptation to UHI should be directed toward the integrated strengthening of micro-ecosystem functions. These findings are expected to provide a scientific basis for the development of micro-ecosystem–based adaptation strategies in sustainable urban environmental planning and management.